Aggregology: Exploration and innovation at aggregate level. Issue 1 (29th December 2020) - Tang, Ben Zhong
Abstract : An aggregate is not a simple mixture of its molecular constituents. Understanding the operations and interplays of various forces and processes involved in an aggregate system is of great academic value and has far‐reaching practical implications. We are launching Aggregate with the aim of building a new platform for aggregology study and in the hope to open up new avenues for explorations at higher levels of structural hierarchy and system complexity.